ЗГУРТОВАНІСТЬ КОЛЕКТИВУ В УМОВАХ КАРАНТИНУ: ВПЛИВ COVID-19 НА ОРГАНІЗАЦІЮ ПРАЦІ В УКРАЇНІ - Todoruk, Sergy; Kobelia, Zoriana (My University, 2023)
У статті досліджено вплив пандемії коронавірусу та інформації про хворобу на трудову активність в Україні, коли роботодавці прийняли рішення про призупинення діяльності підприємств або переведення їх на дистанційну форму роботи, що в умовах вимушеної соціальної самоізоляції призвело до проблем комунікації людей. Розглянуто вплив пандемії COVID-19 на організацію праці в Україні в цілому та на згуртованість колективу, зокрема, в умовах карантину, виділено заходи, що допоможуть нівелювати негативні чинники, що впливають на працівників в умовах карантину та покращити згуртованість колективу, зазначено заходи, що були впроваджені з боку держави. Визначено суть та методику розрахунку показників згуртованості, описані основні чинники впливу на згуртованість трудових колективів. Досліджено ситуацію на ринку праці, зокрема проаналізовано рівень безробіття до та під час пандемії з визначенням основних видів економічної діяльності, які постраждали від карантину найбільше. Запропоновано найдієвіші засоби комунікації колективу при «віддаленій» роботі – дистанційні зустрічі, веб-конференції, онлайн наради, вебінари. Розглянуто зміни, яких зазнав робочий процес в умовах карантину, як вплинула самоізоляція та дистанційна форма роботи на працездатне населення нашої держави та запропоновані заходи, що можуть підвищити згуртованість колективу в даних умовах. Доведено, що створення сприятливого психологічного клімату є важливим завданням ефективної організації, коли і керівники, і працівники усвідомлюють відповідальність за психологічне та емоційне благополуччя колективу і працюють над досягненням цієї мети.
COHERENCE OF THE LABOR TEAM UNDER QUARANTINE CONDITIONS: IMPACT OF COVID-19 ON THE ORGANIZATION OF LABOR IN UKRAINE
The article considers the impact of the coronavirus pandemic and information about the disease on labor activity in Ukraine, when all employers of our country decided to suspend the activities of enterprises or transfer them to a remote form of work, which in the conditions of forced social self-isolation led to problems with people's communication. The impact of the COVID-19 pandemic on the organization of labor in Ukraine as a whole, and on labor team cohesion, in particular, in quarantine restrictions conditions is considered, measures are highlighted that will help to eliminate negative factors harmful affecting workers in quarantine conditions and improve team cohesion and notes the measures implemented by the state authorities. The essence and method of calculation are determined, the main factors affecting the cohesion of labor teams are described. The situation on the labor market of Ukraine was studied, in particular, the level of unemployment before and during the pandemic was analyzed with the identification of the main types of economic activity that were most affected by the quarantine restrictions. The most effective means of team communication during "remote" work are offered by the authors - remote meetings, web conferences, online meetings, webinars. The changes that the working process under quarantine has undergone, how self-isolation and remote form of work have affected the able-bodied population of our state were also considered by the authors and proposed measures that can increase the cohesion of the team in these conditions. It has been proven by the authors that creating a favorable psychological climate is an important task of an effective organization, when both managers and employees are aware of the responsibility for the psychological and emotional well-being of the team and work to achieve this goal. It is also noted that Ukrainian business has always been in a state of upheaval and experienced relatively difficult times. Many businesses have adapted to the crisis, and the experience of the crisis during and after the pandemic did not come as a surprise to small and medium-sized businesses. In general, most businesses continued to operate, create jobs and pay taxes. Business learned to work under such conditions and did not collapse as precipitously as after a full-scale invasion.
Keywords: COVID-19; згуртованість; безробіття; колектив; дистанційна форма роботи; cohesion; self-isolation; quarantine; remote form of work